The contribution of VEGF signalling to fostamatinib‐induced blood pressure elevation. (May 2014) - Skinner, M; Philp, K; Lengel, D; Coverley, L; Lamm Bergström, E; Glaves, P; Musgrove, H; Prior, H; Braddock, M; Huby, R; Curwen, J O; Duffy, P; et al.
<x xml:space="preserve">Abstract</x> Background and Purpose Fostamatinib is an inhibitor of spleen tyrosine kinase (TK). In patients, fostamatinib treatment was associated with increased BP. Some TK inhibitors cause BP elevation, by inhibiting the VEGF receptor 2 (VEGFR2). Here, we have assessed the mechanistic link between fostamatinib‐induced BP elevation and inhibition of VEGF signalling. Experimental Approach We used conscious rats with automated blood sampling and radio telemetry and anaesthetized rats to measure cardiovascular changes. Rat isolated aorta and isolated hearts, and human resistance vessels in vitro were also used. NO production by human microvascular endothelial cells was measured with the NO‐dependent probe, DAF‐FM and VEGFR2 phosphorylation was determined in mouse lung, ex vivo. Key Results In conscious rats, fostamatinib dose‐dependently increased BP. The time course of the BP effect correlated closely with the plasma concentrations of R406 (the active metabolite of fostamatinib). In anaesthetized rats, infusion of R406 increased BP and decreased femoral arterial conductance. Endothelial function was unaffected, as infusion of R406 did not inhibit hyperaemia‐ or ACh‐induced vasodilatation in rats. R406 did not affect contraction of isolated blood vessels. R406 inhibited VEGF‐stimulated NO production from human endothelial cells in vitro, and treatment with R406 inhibited VEGFR2 phosphorylation in vivo. R406 inhibited VEGF‐induced hypotension in anaesthetized rats. Conclusions and Implications Increased vascular resistance, secondary to reduced VEGF‐induced NO release from endothelium, may contribute to BP increases observed with fostamatanib. This is consistent with the elevated BP induced by other drugs inhibiting VEGF signalling, although the contribution of other mechanisms cannot be excluded.